Crystal Structure Regulation of CoSe2 Induced by Fe Dopant for Promoted Surface Reconstitution toward Energetic Oxygen Evolution Reaction - Chen, Shuo; Yue, Kaiqin; Shi, Jiawei; Zheng, Zhicheng; He, Yuanqing; Wan, Hao; Chen, Gen; Zhang, Ning; Liu, Xiaohe; Ma, Renzhi (Inorganic Chemistry, 2024)
Most nonoxide catalysts based on transition metal elements will inevitably change their primitive phases under anodic oxidation conditions in alkaline media. Establishing a relationship between the bulk phase and surface evolution is imperative to reveal the intrinsic catalytic active sites. In this work, it is demonstrated that the introduction of Fe facilitates the phase transition of orthorhombic CoSe2 into its cubic counterpart and then accelerates the Co–Fe hydroxide layer generation on the surface during electrocatalytic oxygen evolution reaction (OER). As a result, the Fe-doped cubic CoSe2 catalyst exhibits a significantly enhanced activity with a considerable overpotential decrease of 79.9 and 66.9 mV to deliver 10 mA·cm–2 accompanied by a Tafel slope of 48.0 mV·dec–1 toward OER when compared to orthorhombic CoSe2 and Fe-doped orthorhombic CoSe2, respectively. Density functional theory (DFT) calculations reveal that the introduction of Fe on the surface hydroxide layers will tune electron density around Co atoms and raise the d-band center. These findings will provide deep insights into the surface reconstitution of the OER electrocatalysts based on transition metal elements.